A case study of development and utilization of urban underground space in Shenzhen and the Guangdong-Hong Kong-Macao Greater Bay Area - Xie, Heping; Zhang, Yanhui; Chen, Yiyan; Peng, Qi; Liao, Zhiyi; Zhu, Jianbo (Tunnelling and underground space technology, 2021)
•Future trends in the exploitation of urban underground space were predicted.•Conceptualization for the exploitation of urban underground space in Shenzhen was proposed.•Strategy for the exploitation of underground space in the GHMGB area was presented. The 21st century has been a period characterized by the rapid development and utilization of underground space together with urbanization. Shenzhen is the model city of rapid development in China, and the Guangdong-Hong Kong-Macao Greater Bay Area (GHMGB area) is one of four major bay areas worldwide. It is commonly acknowledged that the exploitation of urban underground space helps to alleviate various problems accompanying urbanization. It is critically important to define a comprehensive master plan and to conceptualize the development and utilization of urban underground space in large cities such as Shenzhen and in metropolitan areas such as the GHMGB area. In this paper, a strategy for and a conceptualization of the development and utilization of urban underground space are proposed. Based on a review, it is concluded that the future exploitation of urban underground space will reflect the following trends: sustainability, integration, deep exploitation, ecologicalization, informatization and humanization. Subsequently, in accordance with these trends, a four-step blueprint was proposed for the development and utilization of Shenzhen’s underground space, and the corresponding strategies and technical support systems were presented. The four strategies include spatiotemporal planning, coordinated development, green ecology and intelligent management, and the associated technical support systems address underground space ecological cycling, green energy self-cycling and low-carbon maintenance, Internet of Things (IoT) intelligent management, and stability and disaster prevention and control. Because the sustainable development and utilization of underground space are inevitably accompanied by the establishment of an underground green energy system, e.g., wind energy, solar energy, nuclear energy, ocean energy and, in particular, geothermal energy, a scheme for underground green energy systems was proposed. In addition, a three-stage development strategy and zoning plan for the development and utilization of underground space in the GHMGB area were presented. The findings in this paper could offer guidelines for the future development and utilization of urban underground space in large cities worldwide.